Establishment of a Cell Culture Model Permissive for Infection by Hepatitis B and C Viruses - Otoguro, Teruhime (Hepatol Commun, 2020)
Compared with each monoinfection, coinfection with hepatitis B virus (HBV) and hepatitis C virus (HCV) is well known to increase the risks of developing liver cirrhosis and hepatocellular carcinoma. However, the mechanism by which HBV/HCV coinfection is established in hepatocytes is not well understood. Common cell culture models for coinfection are required to examine viral propagation. In this study, we aimed to establish a cell line permissive for both HBV and HCV infection. We first prepared a HepG2 cell line expressing sodium taurocholate cotransporting polypeptide, an HBV receptor, and then selected a cell line highly permissive for HBV infection, G2/NT18‐B. After transduction with a lentivirus‐encoding microRNA‐122, the cell line harboring the highest level of replicon RNA was selected and then treated with anti‐HCV compounds to eliminate the replicon RNA. The resulting cured cell line was transduced with a plasmid‐encoding CD81. The cell line permissive for HCV infection was cloned and then designated the G2BC‐C2 cell line, which exhibited permissiveness for HBV and HCV propagation. JAK inhibitor I potentiated the HCV superinfection of HBV‐infected cells, and fluorescence‐activated cell‐sorting analysis indicated that HBV/HCV double‐positive cells accounted for approximately 30% of the coinfected cells. Among several host genes tested, cyclooxygenase‐2 showed synergistic induction by coinfection compared with each monoinfection. Conclusion: These data indicate that our in vitro HBV/HCV coinfection system provides an easy‐to‐use platform for the study of host and viral responses against coinfection and the development of antiviral agents targeting HBV and HCV.